A cross-sectional survey on cold chain management of vaccines in Cebu, Philippines - Maglasang PL; Butalid ML; Pastoril MF; Pratama AN; Tan EY (Centro de Investigaciones y Publicaciones Farmaceuticas, 2018)
Background: Appropriate cold chain management is the foundation of safety and quality of vaccines. Objectives: This cross-sectional study was conducted to assess the cold chain management of the rural health units of Consolacion and Liloan, Cebu, Philippines on August to September 2017. Methods: Data was collected using a structured questionnaire, which was developed based on previous studies of cold chain survey. The questionnaire was administered to one personnel who is responsible for the storage and maintenance of vaccines in each public health center (PHC). Results: Of 42 targeted PHCs, only 52.4% (n=22) agreed to join in the study. The results of the study indicated that storage units and equipments were available in all 22 PHCs, even though only five of them (22.7%) stored vaccines. The majority of PHCs (90.9%, n=20) did not have access to a generator and only 9% (n=2) had a voltage stabilizer connected to the refrigerator. Refrigerators that were equipped with thermometer were only found in 68.2% (n=15) PHCs. No statistically significant relationship was found (p=0.159) between the statuses of PHCs to store vaccine and the level of knowledge of health professionals assigned to manage the vaccine. Conclusions: Primary health centers that store vaccines have at least one functional refrigerator and freezer and alternative power sources. Contingency plans in the event of mechanical and power failure as well as proper temperature monitoring are needed. Personnel handling vaccines must be updated on proper storage and transport of such like the use of cold boxes and ice packs to maintain cold chain. Improvement of cold-chain management for vaccines in Cebu City's PHCs was necessary.